The Fifth International Conference on VLSI Design
DOI: 10.1109/icvd.1992.658067
|View full text |Cite
|
Sign up to set email alerts
|

Use of CMOS Technology in Wave Pipelining

Abstract: Wave pipelining is a technique for pipelining digital systems that can increase the clock frequency without increasing the number of storage elements. This is achieved by clocking the system faster than the propagation delay between storage elements. The design of such systems is more difficult because all paths in the combinational logic must have about equal delay. To implement wave pipelining, some technologies seem to be better than others depending on the delay properties. Static CMOS has the disadvantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The study reported in [10] shows that under proper design constraints, the overall delay variation of a conventional static CMOS circuit is relatively small, despite substantial variations of a single CMOS gate. For a 4-bit adder slice, the worst-case delay variation is about 10%.…”
Section: Cmos Wave Pipeliningmentioning
confidence: 98%
See 1 more Smart Citation
“…The study reported in [10] shows that under proper design constraints, the overall delay variation of a conventional static CMOS circuit is relatively small, despite substantial variations of a single CMOS gate. For a 4-bit adder slice, the worst-case delay variation is about 10%.…”
Section: Cmos Wave Pipeliningmentioning
confidence: 98%
“…We have adopted the design constraints reported in [10] in order to minimize delay variations for CMOS. Therefore, only 2-input NAND gates and inverters are used for the synthesis of our wave-pipelined multiplier.…”
Section: Cmos Wave Pipeliningmentioning
confidence: 99%
“…The effect is more pronounced in the case of complex gates having varying number of stacked transistors in different parallel paths. Klass and Mulder [7] have proposed to use a modified two-input NAND gate in static CMOS as the basic building block of wave pipelined digital systems. Gray et al [8] propose to use cross coupled two-input pseudo-nMOS NAND gates.…”
Section: Selection Of the Logic Stylementioning
confidence: 99%